I HUBUNGAN LEMBAR KERJA PESAPEAN BERBASIS STEAM DAN MOTIVASI GURU TERHADAP AKTIVITAS BELAJAR SISWA DI KABUPATEN SAMPANG: Lembar Kerja STEAM , Motivasi guru, Aktivitas siswa - Indrawati (Journal of Education Management and Learning, 2020)
This study aims to determine the relationship of Pesaean Worksheet Berbasis STEAM and Teacher Motivation of Student Learning Activities at This research is a quantitative research with a population and sample of 88 science teachers consisting of 5 private teachers and 83 public teachers. with a population and sample of 88 science teachers consisting of 5 private teachers and 83 public teachers. Data collection techniques using a questionnaire with quantitative analysis using correlation and regression tests. The results showed that the Worksheet had an effect on student learning activities. This influence can be seen from the results of data processing which shows the tcount value of STEAM-based pesapesan worksheet of 5.257> 1.988 with Sig value of 0.000 <0.05 while the effect is 85, the remaining 15% is influenced by other factors outside this study. Likewise with teacher motivation has a significant effect on student activity with a tcount of 5.728> 1.988 with an influence of 85%, the remaining 15% is influenced by other factors outside this study. The Relationship between STEAM-Based Study Worksheets and student teacher motivation has a significant effect on learning activities with a calculated value of 12.895> 3.098 with a significant value of 0.000 <0.05. While the effect is 76.3%, the remaining 23.7% is influenced by other factors outside this study